ANALISIS PENATALAKSANAAN ASUHAN KEBIDANAN KEHAMILAN PADA NY.A DENGAN KETUBAN PECAH DINI DI PUSKESMAS PAGAR MERBAU KABUPATEN DELI SERDANG TAHUN 2019 - MARLINA RAJAGUKGUK (JURNAL ILMIAH KOHESI, 2020)
The main principle of management is to prevent perinatal mortility and morbidity in both mothers and babies that canincrease due to infection or due to preterm birth < 37 weeks. Most patients (90%) spontaneous delivery within 24 hours. Themanagement of the patient depends on their wishes but the mother's risk of intrauterine infection should be remembered.The risk of intra-uterine infection will increase. Pregnancy is a condition in which a woman has a growing fetus in her body(which is generally in the womb). Pregnancy in humans ranges from 40 weeks or 9 months, calculated from the beginning ofthe last menstrual period until childbirth. Early ruptured amniotics occurs in 6-19% of pregnancies. The incidence of earlyruptured amniotics ranges from 8-10% in aterm or sufficiently monthly pregnancies, whereas in preterm pregnancies there isa 1% pregnancy. In pregnancy aterm 90% occurs birth within 24 hours after amniotic rupture. At 28-34 weeks gestation 50%of childbirth occurs within 24 hours and at pregnancy less than 26 weeks of childbirth occurs within 1 week. The risk ofamniotic rupture early can cause some problems for the mother as well as for the fetus. For mothers it can cause intrapartalinfections (in childbirth), puerparalis infections (nifas period), old partus, bleeding, postpartum, morbidity, and maternalmortality. As for infants it can cause prematurity, funiculli prolapse (decrease in umbilical cord, hypoxia, secondary asphyxia,fetal deformity syndrome, morbidity, and perinatal mortality.